Tracing the relationship between inequality, crime and punishment : space, time and politics - Lacey, Nicola; Soskice, David W., 1942-; Cheliotis, Leonidas K., 1977-; Xenakis, Sappho, 1976- (Oxford : Published for the British Academy by Oxford University Press, 2021)
The question of inequality has moved decisively to the top of the contemporary intellectual agenda. Going beyond Thomas Piketty's focus on wealth, increasing inequalities of various kinds, and their impact on social, political and economic life, now present themselves among the most urgent issues facing scholars in the humanities and the social sciences. Key among these is the relationship between inequality, crime and punishment. The propositions that social inequality shapes crime and punishment, and that crime and punishment themselves cause or exacerbate inequality, are conventional wisdom. Yet, paradoxically, they are also controversial. In this volume, historians, criminologists, lawyers, sociologists and political scientists come together to try to solve this paradox by unpacking these relationships in different contexts.
This edition previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 19, 2021).
Keywords: Crime -- Sociological aspects; Equality; Corrections -- Social aspects; True Crime; Social services & welfare, criminology